Rozwój rynków finansowych a działalność inwestycyjna zakładów ubezpieczeń w Polsce - Szkarłat, Anna (The Development of the Financial Market and the Investment Portfolio of the Polish Insurance Sector, 2008)
Polish insurance market has been one of the most dynamically developing industries of the Polish economy. In particular, the growing accumulation of capital in the insurance industry results in situation when insurance companies are one of the most active participants of Polish financial markets. The key problem is what kind of factors determines the investments activity of this sector. Being aware of numerous law restriction on investments activity of insurance companies, the author describes the development of Polish financial markets as a main factor influencing investments activity of insurance sector. The investments portfolio structure of the Polish insurance sector reflects the structure of the Polish capital market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 420-427